2022
DOI: 10.3389/fimmu.2022.886226
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Pemphigus Autoantibodies Against C-terminus of Desmoplakin Induced Acantholysis In Vitro and In Vivo

Abstract: Paraneoplastic pemphigus (PNP) is an autoimmune bullous disease associated with underlying neoplasms and characterized by antibodies against desmoglein 3 (Dsg 3) and plakins. Autoantibodies against desmoglein 3 in sera of patients with PNP have been proven to cause acantholysis in vivo in neonatal mice. As a member of the plakin family, autoantibodies against desmoplakin were detected frequently by immunoprecipitation in the sera of PNP. The recombinant C-terminus of desmoplakin was expressed and purified to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…One study reported that purified anti‐desmoplakin antibody from a patient with PNP induced dissociation of keratinocytes in vitro and caused blisters in vivo when transferred to neonatal mice. A possibility that the contaminated anti‐Dsg3 antibody in the purified antibodies could cause blister formation remains elucidated 65 . And the potential pathogenicity of monoclonal antibodies against plakin family proteins has not yet been investigated.…”
Section: Pathogenic Role Of Autoreactive T Cells In Pnpmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported that purified anti‐desmoplakin antibody from a patient with PNP induced dissociation of keratinocytes in vitro and caused blisters in vivo when transferred to neonatal mice. A possibility that the contaminated anti‐Dsg3 antibody in the purified antibodies could cause blister formation remains elucidated 65 . And the potential pathogenicity of monoclonal antibodies against plakin family proteins has not yet been investigated.…”
Section: Pathogenic Role Of Autoreactive T Cells In Pnpmentioning
confidence: 99%
“…A possibility that the contaminated anti‐Dsg3 antibody in the purified antibodies could cause blister formation remains elucidated. 65 And the potential pathogenicity of monoclonal antibodies against plakin family proteins has not yet been investigated. Clinically, it is often observed that severe mucosal lesions persist even after the Dsg3 antibody becomes undetectable due to treatment, suggesting that cell‐mediated immune responses recognized in pathology and humoral immunity are crucial aspects to consider in the pathogenesis of PNP.…”
Section: Pathogenic Role Of Autoreactive T Cells In Pnpmentioning
confidence: 99%